Pseudohypoparathyroidism during pregnancy and the postpartum period: A case series of five patients - Wang, Jia-Jia; Yang, Yi; Wang, Ya-Bing; Song, An; Jiang, Yan; Li, Mei; Xia, Wei-Bo; Liu, Yan-Ping; Wang, Ou; Xing, Xiao-Ping (Frontiers in Endocrinology, 2022)
Objectives: Pseudohypoparathyroidism (PHP) is a rare disease, especially when combined with pregnancy. We aimed to explore the changes of serum calcium/parathyroid hormone (PTH) level and medical treatment in a case series of PHP during pregnancy and postpartum period. Methods: A total of 5 PHP patients with 6 pregnancies were enrolled. Classification of PHP was based on (epi)genetic analysis. Clinical characteristics, biochemical indices and treatment strategies before, during and after pregnancy were retrospectively collected. Results: All patients received calcium and vitamin D agents with nearly normal serum calcium before pregnancy except patient 2 who was found hypocalcaemia during gestation. All patients chose caesarean section and one suffered preterm delivery due to oligoamnios. The neonatal birth weight ranged from 2250g to 4300g and all neonates were free of hypocalcaemia related symptoms. The change in calcium metabolism was inconsistent including stable, improved, or worsened during pregnancy among them. Serum PTH level remained low in the first two trimesters in patients with stable and improved condition while increased in the last two trimesters in patients with worsened condition. Serum calcium changed inconsistently while PTH increased consistently during lactation. For patients who did not breastfeed, the calcium homeostasis improved after delivery. Conclusion: Calcium homeostasis and medicine dosage changed differently in PHP patients during pregnancy and lactation. However, most patients had good pregnancy outcomes. Serum PTH level might predict the changes of calcium metabolism during pregnancy.